Implementation of the Disaster-Based “Make A Match” Learning Model on Interest and Learning Independence of Islamic Private High School Students - Nurul Infitah; Tony Wijaya (STAI Hubbulwathan Duri, 2022)
This study aims to determine the application of the Disaster based Make a Match learning model regarding student interest and learning independence. The type of this study is quasi-experimental by designing a non-equivalent, post-test only control group. The research subjects were class XI IPS Islamic private high school students in Jember Regency. The analysis of the data used is descriptive statistics and the Mann-Whitney test. As a result, the average learning interest score of the control class was 19.95, and the experimental class was 26.20. Hence, the average learning interest score of the experimental class was higher than that of the control class. Similarly, the average score of learning independence in the experimental class is more critical than in the control class. The control score is 17.35, and the experimental score is 34.20. The hypothesis test results showed a significant difference between the two groups using the Disaster based Make A Match learning model and the traditional learning model. The research concludes that students' interest and independence in learning using the disaster-based make a match learning model is more significant than in the conventional learning model.